BIMBINGAN BELAJAR BAHASA INGGRIS BAGI ANAK USIA SEKOLAH DASAR (6-12 TAHUN) DI DESA SEMANGAT DALAM RT.31HANDIL BHAKTI - Dewi Rosaria; Hartatya Novika (Universitas Islam kalimantan MAB, 2017)
This community service activity was in the form of English tutoring at Semangat Dalam village RT.31Handil Bhakti. The objectives are 1) to know the proper way to provide English tutoring for primary school age children in Semangat Dalam village, 2) to know that Englis tutoring is effective for primary school age children. This activity used 3 (three) methods, such as lectures, discussion, and games. The results of this tutoring activity are 1) it is known that primary school age children (6-12 years of age) were more enthusiastic and they were able to follow and understand the material when team taught them using games method in particular by singing songs related to the material.They become more confident to introduce themselves using English in front of their friends. 2) tutoring is effective enough to help primary school age children in Semangat Dalam village to increase their knowledge and understanding of English lessons, as well as increase their confidence in using English.